Sacrum słowem sławione – terminologia religijna w twórczości Owidiusza - Kaczor, Idaliana (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2019)
The article investigates Ovid’s use of religious terminology and imagery, in particular in the Fasti and the Metamorphoses. As an educated Roman citizen, Ovid was conversant with Roman ritual practices and frequently drew on facets of the Roman religious experience in his writing, exploring topics such as ritual performance, religious nomenclature, festivals, customs and traditions. In the article, I argue that Ovid’s treatment of religious material is deliberately uneven. The poet, well-versed in the Roman ritual nomenclature, nevertheless flaunted his technical competence only in the rite-oriented Fasti: in his other works, above all in the myth-laden Metamorphoses, he abandoned drier technical details for artistic flair and poetic imagery, unconstrained by traditional practices of Roman piety. The mythological setting of the latter poem gave Ovid a chance to comment upon universal truths of human nature, espousing the prevailing Roman belief that maintaining good relations with the gods (pax deorum) through collective piety would win Rome divine favour in all her initiatives.